Stakeholder perceptions of the benefits and barriers of implementing environmental management systems in the Nigerian construction industry - Owolana, Victoria O.; Booth, Colin A. (Journal of Environmental Engineering and Landscape Management, 2016)
This study investigates stakeholder opinions of the major benefits and barriers of Environmental Management Systems (EMS) to the Nigerian construction industry, and the perceived issues to EMS adoption among organisations in the industry. The study highlights the environment as an important stakeholder in the industry because it affects and is affected by construction activities on a regular basis. It identifies the importance of ISO 14001 in ensuring adequate consideration for the environment is maintained on construction projects. The research adopts a quantitative approach by analysing responses from an online survey among construction industry professionals in Nigeria. The questions on the survey were drawn from a similar study carried out in Asia and the results were analysed using the Weighted Average and Standard Deviation statistical approach. Results reveal that the major benefits of EMS to the Nigerian construction industry were improved efficiency in waste management and environmental protection, as well as an overall increase in employee motivation due to better opportunities for training and development. Lack of technological support in organisations and the high cost of implementing EMS were viewed as the major barriers towards its uptake in construction companies. The findings also indicate that a feasible EMS implementation strategy must not ignore the unique nature of the Nigerian construction industry, which comprises mostly small and medium enterprises. The study concludes by recommending the use of a waste management plan based on the Reuse-reducerecycle-Recover model and an employee training plan to ensure continuous improvement in the organisation’s environmental management strategy.